Digital Literacy Trends in Islamic Perspective in Higher Education: A Bibliometric Review - Mohamad Fauzan Adima; Baharudin; Imam Syafe'i; Siti Zulaikha; Beti Susilawati; Qonita Shabira (Postgraduate, University of Mataram, 2024)
This study examines trends in digital literacy research within higher education from an Islamic perspective while identifying opportunities for its development. Employing a Systematic Literature Review (SLR) method, 188 articles were sourced from Scopus, Sinta 1, and Sinta 2 databases, with 37 articles published between 2019 and 2024 meeting the inclusion criteria for analysis. Guided by the PRISMA framework, the review ensured the validity and reliability of findings, while bibliometric analysis was conducted using VOSviewer 1.6.20. The analysis revealed a sharp increase in publications during 2021, attributed to the rapid digital transformation of higher education amid the COVID-19 pandemic. However, it also highlighted a significant gap in integrating Islamic education with digital technology, despite its potential to improve learning outcomes and quality. The majority of publications originated from Indonesia, China, and Russia, with both quantitative and qualitative approaches dominating the methodologies. These findings offer valuable insights into the evolving landscape of digital literacy in higher education and emphasize the critical need for further research to advance its holistic development.